SIMULASI EKSPLORASI WEB MENGGUNAKA NW3AF DAN WEB GOAT SERTA ALTERNATIF PENCEGAHANNYA - Ahmad Sanmorino (UNIVERSITAS INDO GLOBAL MANDIRI)
Exploration web is the means used to obtain information on a web page specifically related to security issues. In this research, exploratory simulation tool W3AF danWebGoat.W3AF web use is short for Web Application Attack and Audit Framework. The objective of this application is as a framework to find the weakness of web applications. While Web Goat is a web page that is targeted for exploration on the environment localhost. Simulation gives positive results of various web pages of information targeted exploration. Among the security loopholes that can be used as roads by the cracker to commit an illegal act. Alternative solutions provided in order to close the security gap, so as to minimize the risk r a crime that may occur.Key words : web exploration, W3AF, webgoat